2012
DOI: 10.11646/zootaxa.3281.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Review of the genus Phlugiolopsis Zeuner, 1940 (Orthoptera: Tettigoniidae: Meconematinae) from China

Abstract: This paper reviews the genus Phlugiolopsis Zeuner, 1940, and describes 5 new species from China, Phlugiolopsis pectinissp. nov., Phlugiolopsis tribranchis sp. nov., Phlugiolopsis digitusis sp. nov., Phlugiolopsis trullis sp. nov. andPhlugiolopsis adentis sp. nov. A key to the species and distributional data in China are given. The type specimens are deposited in the Museum of Hebei University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Acosmetura possibly differs from the previous "taxa" in the male genitalia sclerotized (Bian et al 2014); but for majority of species including in Phlugiolopsis, Tettigoniopsis, and Cosmetura, the male genital structure is not studied. Omkoiana sensu Helfert and Sänger (2002) is practically indistinguishable from the genus Phlugiolopsis sensu all the later authors (Wang et al 2012;Bian et al 2012aBian et al , 2012bBian et al , 2013Bian and Shi 2018) but differs from some species of this genus and from the other aforementioned "taxa" by a strongly specialized distal half of the male genital plate; however, similar (but usually less strong) and probably homologous specializations are developed in some other species of Phlugiolopsis s. l. In the latest paper (Bian and Shi 2018), the latter closely related species were divided into three new subgenera (Longiloba, Tribranchis, and Uncinata), but differences between these subgenera are insufficiently understandable.…”
Section: Introductionmentioning
confidence: 86%
“…Acosmetura possibly differs from the previous "taxa" in the male genitalia sclerotized (Bian et al 2014); but for majority of species including in Phlugiolopsis, Tettigoniopsis, and Cosmetura, the male genital structure is not studied. Omkoiana sensu Helfert and Sänger (2002) is practically indistinguishable from the genus Phlugiolopsis sensu all the later authors (Wang et al 2012;Bian et al 2012aBian et al , 2012bBian et al , 2013Bian and Shi 2018) but differs from some species of this genus and from the other aforementioned "taxa" by a strongly specialized distal half of the male genital plate; however, similar (but usually less strong) and probably homologous specializations are developed in some other species of Phlugiolopsis s. l. In the latest paper (Bian and Shi 2018), the latter closely related species were divided into three new subgenera (Longiloba, Tribranchis, and Uncinata), but differences between these subgenera are insufficiently understandable.…”
Section: Introductionmentioning
confidence: 86%
“…et al 2012Wang H.Q. et al , 2015a, especially brachypterous groups, most of which occur in South, Southwest and Central China (Bian et al 2012a(Bian et al , 2012b(Bian et al , 2013Wang H.Q. et al 2015b;Cui et al 2019Cui et al , 2020Wang T. et al 2019aWang T. et al , 2019bWang T. et al , 2020aWang T. et al , 2020bWang T. et al , 2020c.…”
Section: Introductionmentioning
confidence: 99%
“…et al , 2015b, where some new genera and many new species are still being discovered (Gorochov 2019;Chen et al 2019;Cui et al 2019Cui et al , 2020Wang T. et al 2019aWang T. et al , 2019bWang T. et al , 2020aWang T. et al , 2020b. Some genera and species are endemic to China (Liu & Zhou 2007;Bian et al 2012aBian et al , 2012bBian et al , 2013Bian et al , 2014Bian et al , 2017Shi & Bian 2012Wang H.Q. et al 2012Wang H.Q.…”
Section: Introductionmentioning
confidence: 99%
“…We examined some specimens of Phlugiolopsis jinyunensis (Shi & Zheng, 1994) from the type locality and indicated that it has similar characters with Acosmetura, but differs from Phlugiolopsis in: male left stridulatory area large, stridulatory file approximately straight without 1 digitated process at basal area, male genitalia sclerotized and shorter (Bian et al, 2012a(Bian et al, , 2012b(Bian et al, , 2013. Based on these characters, we transferred Phlugiolopsis jinyunensis (Shi & Zheng, 1994) to Acosmetura.…”
Section: Introductionmentioning
confidence: 99%
“…The measuring method follows previous convention (Bian et al, 2012a), except female body length, the distance of which is from apex of fastigium verticis to the apex of ovipositor.…”
Section: Introductionmentioning
confidence: 99%